Process for synthesizing large-size cultivated diamond by utilizing double-layer carbon source structure HPHT method
Through the optimization of the double-layer carbon source structure and process, the problems of inconsistent carbon source concentration and stress release in the HPHT method are solved, and the stable growth and high-clearity finished products of high-quality large-size diamonds are achieved, which are suitable for the application of diamonds in the functional field.
Patent Information
- Application Number
- CN202411198832.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
In the high temperature and high pressure method (HPHT), excessive or too small carbon source concentration gradient will affect the growth quality of diamond large single crystals, and defects such as cracks are easily generated during the pressure relief stage, making it difficult to achieve economical production of high-quality large-size diamonds.
Using the double-layer carbon source structure and differential carbon source formula, large single crystals of diamond of 50ct or above were prepared by adjusting the process parameters and combining the synthesis process curve. Large-size incubation diamonds were synthesized by the HPHT method of the double-layer carbon source structure, including preparation Carbon source I and carbon source II, the alloy catalyst is assembled into blocks, synthesised at high temperature and high pressure, and impurities are removed by pickling, and the synthesis process is optimized to control carbon source concentration and stress release.
It achieves stable growth of large-size diamond single crystals with high clarity and low impurities, reduces crack defects, improves yield, and provides technical support for the application of diamond in the functional field.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of superhard material synthesis, and in particular to an assembly structure and process technology capable of stably growing large-sized cultured diamonds. The present invention specifically relates to a process for synthesizing large-sized cultured diamonds by the HPHT method using a double-layer carbon source structure. The present invention can provide technical support for the HPHT synthesis of large-sized cultured diamonds. Background Art
[0002] Cultured diamonds have been loved by the public in recent years due to their sustainability, price advantages and environmental advantages, and the global production of cultured diamonds has maintained a sustained growth trend. Based on the technical principles, the current global cultured diamond synthesis technology can be divided into two categories: high pressure and high temperature method (HPHT) and chemical vapor deposition method (CVD). To synthesize large diamond single crystals using chemical vapor deposition, natural diamonds, HPHT diamond single crystals or CVD diamond single crystals are required as substrates for epitaxial growth. Natural diamonds can guarantee the quality of CVD diamond single crystals and are the most ideal substrate material. However, due to the high price of natural diamonds, HPHT diamond single crystals have become the main source of substrates in the CVD synthesis method. Therefore, in the research and application of large-size cultured diamonds, the research on HPHT synthetic diamond large single crystals plays a key role.
[0003] The temperature gradient method is the main method for synthesizing large single diamond crystals by HPHT. Its principle is as follows: graphite as a carbon source is located at the high temperature end of the cavity, and the seed crystal is located at the low temperature end. Due to the temperature difference between the two, a temperature gradient is formed. The carbon source at the high temperature under HPHT is converted into a diamond structure, and driven by a certain temperature gradient, it diffuses from the high concentration area at the high temperature end to the low concentration area at the low temperature end to achieve growth on the seed crystal. During the growth of high-quality gem-grade large single diamond crystals, if the carbon source concentration gradient is too large, carbon diffuses too fast in the catalyst melt, the seed crystal has insufficient acceptance capacity, and the excess carbon source will grow spontaneously as diamond nuclei or precipitate recrystallized graphite, seriously affecting the quality of the crystal; if the carbon source concentration gradient is too small, the driving force for the diffusion of carbon atoms to the seed crystal is insufficient, causing the growth of diamond single crystals to be slow, which is not conducive to economical production.
[0004] Therefore, the key to growing large-sized cultured diamonds is to reasonably control the concentration of carbon sources. During the decompression stage of synthesis, large-sized cultured diamonds have a greater chance of producing defects such as cracks due to stress release. When designing the synthesis process, it is necessary to fully study the stress release mechanism inside the diamond to eliminate or reduce cracks. Summary of the invention
[0005] The purpose of the present invention is to propose a process for synthesizing large-sized cultivated diamonds by the HPHT method using a double-layer carbon source structure. The process method adopts a double-layer carbon source assembly structure and a differential carbon source formula, and adjusts the synthesis process parameters to solve the key technical problems of carbon source and catalyst ratio and carbon source concentration control. Combined with the matching process curve, large cultivated diamond single crystals of 50 ct and above can be stably prepared, providing technical support for the technological progress of artificially cultivated diamonds and laying a foundation for the application of large-sized diamonds in functional fields.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] A process for synthesizing large-sized cultivated diamond by HPHT method using a double-layer carbon source structure comprises the following steps:
[0008] (1) Preparation of carbon source I, carbon source II and alloy catalyst
[0009] The carbon source I is composed of high-purity graphite powder and Al powder. When specifically prepared, the mass ratio of the high-purity graphite powder to the Al powder is (97-99): (1-3);
[0010] The carbon source II is composed of powdered catalyst powder and high-purity graphite powder. When specifically prepared, the mass ratio of powdered catalyst to high-purity graphite is (55-60): (40-45);
[0011] The alloy catalyst is composed of the following components in mass percentage: Fe 75-80%, Al 15-20%, Ti 1-5%;
[0012] The carbon source I, the carbon source II and the alloy catalyst are made into blocks to facilitate subsequent processing;
[0013] The carbon source I and the carbon source II are prepared by high-speed mixing, granulation, compression molding, vacuum sintering and other processes commonly used in the prior art, and the specific preparation process is not the inventive point of the present invention, so it will not be repeated;
[0014] (2) Synthetic block assembly
[0015] Assembling the carbon source I, carbon source II and alloy catalyst in step (1) into a synthesis block in a certain manner;
[0016] (3) HPHT synthesis
[0017] The synthesis block obtained in step (2) is placed in the synthesis chamber of a six-sided top press for high temperature and high pressure synthesis, the pressure in the synthesis chamber is 6.0-6.5GP, the synthesis temperature is 1200°C-1500°C, and the total synthesis time is 10-20 days;
[0018] (4) After the synthesis is completed, the synthetic block is taken out and impurities are removed by acid washing to obtain a large-sized cultured diamond crystal.
[0019] Preferably, in step (1), the powder catalyst comprises the following raw materials in percentage by weight: Fe 65-70%, Ni 27-34%, 1 <Al≤3%。
[0020] Preferably, the graphite powder used in step (1) is high-purity graphite with a purity of 99.99% and a particle size of 400-600 mesh;
[0021] Fe powder purity: 99.5%-99.9%, particle size 150-200 mesh; Ni powder purity: ≧99.9%, particle size 150-200 mesh; Al powder purity: ≧99.9%, particle size 150-200 mesh.
[0022] Preferably, the assembling step in step (2) is:
[0023] a. Stack carbon source II, alloy catalyst, carbon source I, seed crystal, and thermal conductive sheet in order from top to bottom to form a block, namely a synthetic core column, and cover the outside of the synthetic core column (top surface, bottom surface and surrounding areas) with an insulating cup;
[0024] b. Wrapping the heat-generating carbon tubes (heat-generating materials) around the structure obtained in step a, coating the top and bottom surfaces of the structure with dolomite insulation sheets (insulation materials), and then coating the top and bottom surfaces of the dolomite insulation sheets with heat-generating carbon sheets, and placing the wrapped structure into an insulation tube (e.g., a dolomite insulation liner) to obtain a structure block;
[0025] c. Place the structural block obtained in step b into the cavity of the talc block, and set conductive plugs and insulation rings at the upper and lower ends of the structural block to obtain a synthetic block; the structure and assembly method of the synthetic block in the present invention that are not specifically described can adopt the common methods in the prior art, and are not the inventive point of the present invention, so they will not be repeated.
[0026] Preferably, in step (3), the pressure of the six-sided top press during the synthesis process changes into three stages, as follows: the first stage: the pressure is increased from 0 to P1 (100-120 MPa) within 140-160 seconds, and heating is started when the pressure reaches 30 MPa during the pressure increase process;
[0027] The second stage: the pressure is maintained at P1, and the holding time is set to 10 to 20 days according to the process requirements;
[0028] The third stage: the pressure gradually decreases from P1 to P2 (60-70MPa) within 2000 seconds. At this time, the temperature in the chamber is 900-950℃. The P2 pressure is maintained for 1000-1100 seconds (pressure stabilization stage), and then it is reduced from P2 to 0 within 2000 seconds. At this time, the temperature in the synthesis chamber drops to 350-400℃.
[0029] Preferably, in step (3), the power change and pressure change of the six-sided top press are carried out simultaneously, specifically in three stages, and the power change is as follows:
[0030] The first stage: when the pressure rises to 30 MPA, heating begins. At the same time, the power rises from 0 to W1 within 600 seconds (W1 varies greatly depending on the selected heating element. For the structure and assembly method of the synthesis block in step (2) of the present invention, W1 is usually 7.8-8.0 kW. At this time, the temperature in the synthesis chamber reaches 1200-1350° C.);
[0031] The second stage: when the pressure is maintained at P1, the power increases from W1 to W2 within 10 to 20 days (the power setting value is W2 = W1 + 0.1KW);
[0032] The third stage: as the pressure gradually decreases from P1 to 0, the power decreases from W2 to 0 (at this time, the temperature in the synthesis chamber is between 330-400°C).
[0033] Furthermore, the present invention also provides a large-sized cultivated diamond single crystal synthesized by the HPHT method using a double-layer carbon source structure using the above process.
[0034] The large-sized cultivated diamond single crystal prepared by the present invention has high purity and few impurity elements, and can be prepared into single crystal wafers by laser cutting. It has broad application prospects in cutting-edge science and technology fields such as diamond semiconductor materials, heat dissipation materials, optical grades, and electronic grades.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The double-layer carbon source structure adopted in the present invention is different from the previous design of superimposing a single carbon source and a catalyst. The double-carbon source structure can well solve the problem of inconsistent carbon source concentrations required before and after synthesis, providing sufficient carbon sources and being more suitable for growing large-sized cultured diamonds.
[0037] 2. The double-layer carbon source of the present invention adopts a differential formula. Catalyst powder and denitrification agent (Al powder) are added to the upper carbon source to make up for the insufficient denitrification capacity caused by the rapid growth in the later stage of synthesis, thereby ensuring the color and clarity of the cultured diamond.
[0038] 3. The present invention has also adjusted the supporting synthesis process. In order to adapt to the influence of the double-layer carbon source structure on the growth rate of diamond, a slow temperature rise heating process is designed to provide sufficient power for each stage of cultured diamond growth, better promote the deposition of carbon source on the seed crystal, and is conducive to the growth of larger-sized cultured diamonds; and in the pressure relief stage, a voltage stabilization process is set to solve the problem of cracks in the single crystal caused by stress release, thereby improving the yield rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the assembly structure of the double-layer carbon source of the present invention;
[0040] Figure 1 1. heat conducting sheet; 2. seed crystal; 3. carbon source I; 4. alloy catalyst; 5. carbon source II; 6. heat insulating sheet; 7. heating carbon sheet; 8. conductive plug; 9. heat insulating ring; 10. insulating cup; 11. heating carbon tube; 12. heat insulating tube; 13. pyrophyllite block;
[0041] Figure 2 Schematic diagram of the high temperature and high pressure (HPHT) synthesis process of the present invention;
[0042] Figure 3 This is a weighing chart of large-sized cultured diamond synthesized by the process described in Example 1 of the present invention;
[0043] Figure 4 This is a size measurement diagram of a large-sized cultured diamond synthesized by the process described in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] The graphite powder used in the following examples is high-purity graphite with a purity of 99.99% and a particle size of 400-600 mesh;
[0046] Fe powder purity: 99.5%-99.9%, particle size 150-200 mesh; Ni powder purity: ≧99.9%, particle size 150-200 mesh; Al powder purity: ≧99.9%, particle size 150-200 mesh.
[0047] Example 1
[0048] A process for synthesizing large-sized cultivated diamond by HPHT method using a double-layer carbon source structure specifically comprises the following steps:
[0049] (1) Preparation of carbon source I, carbon source II and alloy catalyst
[0050] Carbon source I is composed of high-purity graphite powder (purity 99.99%) and Al powder. When specifically prepared, the mass ratio of high-purity graphite powder to Al powder is 97:3;
[0051] Carbon source II is composed of powdered catalyst powder and high-purity graphite powder (purity 99.99%). During the specific preparation, the mass ratio of powdered catalyst to high-purity graphite is 55:45;
[0052] The powder catalyst comprises the following raw materials in the following mass percentages: Fe 65%, Ni 33.5%, Al 1.5%;
[0053] The alloy catalyst is composed of the following components in mass percentage: Fe 80%, Al 18%, Ti 2%;
[0054] The carbon source I, the carbon source II and the alloy catalyst are made into blocks to facilitate subsequent processing;
[0055] The carbon source I, carbon source II and alloy catalyst are all prepared by high-speed mixing, granulation, compression molding, vacuum sintering and other processes commonly used in the prior art, and the specific preparation process is not the inventive point of the present invention, so it will not be repeated;
[0056] (2) Synthetic block assembly
[0057] like Figure 1 As shown, carbon source I, carbon source II, and alloy catalyst are assembled into a synthetic block in a certain manner; the specific assembly steps are:
[0058] a. Stack carbon source II 5, alloy catalyst 4, carbon source I 3, seed 2 (diamond seed with a grain size of 70-90 mesh), and heat conductive sheet 1 in order from top to bottom to form a block, i.e., a synthetic core column, and coat the outside of the synthetic core column (top surface, bottom surface and surroundings) with an insulating cup 10; wherein the thickness of carbon source I is 5 mm, the thickness of carbon source II is 10 mm, and the thickness of alloy catalyst is 10 mm;
[0059] b. Wrap the heat-generating carbon tubes 11 (heat-generating material) around the structure obtained in step a, coat the top and bottom surfaces of the structure with dolomite insulation sheets 6 (heat-generating material), then coat the top and bottom surfaces of the dolomite insulation sheets 6 with heat-generating carbon sheets 7, and place the wrapped structure into an insulation tube 12 (e.g., a dolomite insulation liner) to obtain a structure block;
[0060] c. Put the structural block obtained in step b into the cavity of the pyrophyllite block 13, and set the conductive plugs 8 and the insulation ring 9 at the upper and lower ends of the structural block to obtain the synthetic block; the structure and assembly method of the synthetic block in the present invention are not specifically described in the common method in the prior art, and are not the inventive point of the present invention, so they are not described in detail;
[0061] (3) HPHT synthesis
[0062] The synthesis block obtained in step (2) is placed in the synthesis chamber of a six-sided top press for high temperature and high pressure synthesis. The pressure in the synthesis chamber is 6.0-6.5GP, the synthesis temperature is 1200℃-1500℃, and the total synthesis time is 10-20 days. The pressure change and power change of the six-sided top press during the synthesis process are specifically referred to Figure 2 ;
[0063] The specific pressure changes of the six-sided top press are in three stages:
[0064] The first stage: the pressure is increased from 0 to P1 (100MPa) within 160 seconds, and heating begins when the pressure reaches 30MPa during the pressure increase process;
[0065] The second stage: the pressure is maintained at P1, and the holding time is set to 10 days according to the process requirements;
[0066] The third stage: the pressure gradually decreases from P1 to P2 (60MPa, the temperature in the chamber is 900°C) within 2000 seconds, the pressure at P2 is maintained for 1000 seconds (pressure stabilization stage), and then decreases from P2 to 0 within 2000 seconds (the temperature in the synthesis chamber drops to 350°C at this time);
[0067] The power change of the six-sided top press is carried out simultaneously with the pressure change, which is specifically divided into three stages. The power setting of the six-sided top press is:
[0068] The first stage: when the pressure rises to 30 MPA, heating begins. At the same time, the power rises from 0 to W1 within 600 seconds (according to the structure and assembly method of the synthesis block in step (2) of the present invention, the carbon tube 11 is used as the heating element. At this time, W1 is set to 7.8-8.0 kW, and the temperature in the synthesis chamber reaches a maximum of 1300° C.);
[0069] The second stage: when the pressure is maintained at P1, the power increases from W1 to W2 within 10 days (the power setting value is W2 = W1 + 0.1kw);
[0070] The third stage: in the process of gradually reducing the pressure from P1 to 0, the power is reduced from W2 to 0 (at this time, the temperature in the synthesis chamber is reduced from 1300℃ to 350℃);
[0071] (4) After the synthesis is completed, the synthetic block is taken out and impurities are removed by acid washing to obtain a cultured diamond single crystal. After weighing and testing, various indicators such as the size and clarity of the single crystal can be obtained.
[0072] Specifically, the process indicators of the diamond single crystal before and after synthesis in Example 1 are shown in Table 1 and Table 2.
[0073] Table 1: Various indicators of synthetic cultured diamond single crystal before improvement
[0074] Serial number Weight / ct Clarity Chroma crack Blank size / mm 1 35.0 VS E none 16.5*17.0*8.5 2 52.3 SI F Edge crack 20.3*19.5*10.8 3 46.8 SI F none 18.7*18.0*10.2
[0075] Table 2 Various indicators of synthetic cultured diamond single crystals using the process of the present invention (Example 1)
[0076] Serial number Weight / ct Clarity Chroma crack Blank size / mm 1 75.0 VS E none 21.5*20.9*11.6 2 62.8 VS E none 20.8*20.2*11.0 3 82.5 SI E none 23.4*22.5*12.2
[0077] From the data in Tables 1 and 2 above, it can be concluded that: 1. By applying the process method of the present invention, the weight of the large cultured diamond single crystals prepared is significantly increased, and large single crystals of 60 ct and above can be stably obtained, and the corresponding blank size is greatly improved; 2. The internal clarity of the single crystal is improved from SI grade to VS grade; 3. The chromaticity of the single crystal is improved by 1 grade.
[0078] The weight and size parameters of the large-sized cultured diamond synthesized by the process of the present invention are as follows: Figure 3 and Figure 4 As shown, from Figure 3 and Figure 4 It can be concluded that: from the perspective of some of the prepared products, the weight of the single crystal reaches 72.5ct, which is at the leading level in China; the size reaches 23.6mm, and can be cut into single crystal pieces larger than 20mm, meeting some functional application requirements.
[0079] The main innovation of the present invention is that a double-layer carbon source growth structure is designed to provide a stepped concentration of carbon source for the early and late stages of diamond growth, replacing the single-layer carbon source growth method, and in conjunction with a special synthesis process, reducing the generation of defects such as cracks, greatly improving the particle size and growth stability of HPHT synthesized large-size cultured diamonds, the product has high clarity, and the synthesis effect is good.
[0080] Example 2
[0081] Example 2 provides a process for synthesizing large-sized cultivated diamonds by HPHT method using a double-layer carbon source structure. The process method described in Example 2 is different from that in Example 1 in that:
[0082] In step (1), the carbon source I is composed of high-purity graphite powder (purity 99.99%) and Al powder. In the specific preparation, the mass ratio of high-purity graphite powder to Al powder is 98:2;
[0083] Carbon source II is composed of powdered catalyst powder and high-purity graphite powder (purity 99.99%). During the specific preparation, the mass ratio of powdered catalyst to high-purity graphite is 60:40;
[0084] The powder catalyst comprises the following raw materials in the following mass percentages: Fe 70%, Ni 27%, and Al 3%.
[0085] In step (3), the specific pressure change of the six-sided top press is three stages:
[0086] The first stage: the pressure is increased from 0 to P1 (120MPa) within 140 seconds, and heating begins when the pressure reaches 30MPa during the pressure increase process;
[0087] The second stage: the pressure is maintained at P1, and the holding time is set to 20 days according to the process requirements;
[0088] The third stage: the pressure gradually decreases from P1 to P2 (60MPa, the temperature in the chamber is 950°C) within 2000 seconds, the P2 pressure is maintained for 1100 seconds (pressure stabilization stage), and then drops from P2 to 0 within 2000 seconds (the temperature in the synthesis chamber drops to 400°C).
[0089] The power change of the six-sided top press is carried out simultaneously with the pressure change, which is specifically divided into three stages. The power setting of the six-sided top press is:
[0090] The first stage: when the pressure rises to 30 MPA, heating begins. At the same time, the power rises from 0 to W1 within 600 seconds (according to the structure and assembly method of the synthesis block in step (2) of the present invention, the carbon tube 11 is used as the heating element. At this time, W1 is set to 7.8-8.0 kW, and the temperature in the synthesis chamber reaches 1350° C.);
[0091] The second stage: when the pressure is maintained at P1, the power increases from W1 to W2 within 20 days (the power setting value is W2-W1+0.2kw);
[0092] The third stage: in the process of gradually reducing the pressure from P1 to 0, the power is reduced from W2 to 0 (at this time, the temperature in the synthesis chamber is reduced from 1350°C to 400°C).
[0093] Specifically, the process indicators of the diamond single crystal synthesized in Example 2 are shown in Table 3.
[0094] Table 3 Various indicators of synthetic cultured diamond single crystals using the process of the present invention (Example 2)
[0095] Serial number Weight / ct Clarity Chroma crack Blank size / mm 1 73.5 VS E none 23.6*22.1*12.0 2 65.6 VS E none 21.5*20.8*11.2
[0096] From the data in Table 3 above, it can be concluded that: 1. By applying the process method of the present invention, the weight of the large cultured diamond single crystals prepared is significantly increased, and large single crystals of 60 ct and above can be stably obtained, and the corresponding blank size is greatly improved; 2. The internal clarity of the single crystal is improved from SI grade to VS grade; 3. The chromaticity of the single crystal is improved by 1 grade.
[0097] The above describes the specific implementation examples of the present invention. It should be understood that the present invention is not limited to the above specific implementation examples. Those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A process for synthesizing large-sized grown diamonds using a double-layer carbon source structure HPHT method, characterized in that: The steps include: (1) Preparation of carbon source I, carbon source II and alloy catalyst Carbon source I consists of high-purity graphite powder and Al powder, and the mass ratio of high-purity graphite powder to Al powder is (97-99): (1-3); Carbon source II is composed of powdered catalyst powder and high-purity graphite powder, and the mass ratio of powdered catalyst to high-purity graphite is (55-60): (40-45); The alloy catalyst is composed of the following components in mass percentage: Fe 75-80%, Al 15-20%, Ti 1-5%; The carbon source I, the carbon source II and the alloy catalyst are made into blocks; (2) Synthetic block assembly Assemble the carbon source I, carbon source II, and alloy catalyst in step (1) into a synthetic block in a certain manner; (3) HPHT synthesis The synthetic block obtained in step (2) is subjected to high temperature and high pressure synthesis, the synthesis pressure is 6.0-6.5GP, the synthesis temperature is 1200℃-1500℃, and the total synthesis time is 10-20 days; (4) After the synthesis is completed, the synthetic block is taken out and impurities are removed to obtain large-sized cultured diamond crystals.
2. The process according to claim 1, wherein In step (1), the powder catalyst comprises the following raw materials in the following mass percentages: Fe 65-70%, Ni 27-34%, 1 <Al≤3%。 3. The process according to claim 1, wherein The graphite powder used in step (1) is high-purity graphite with a purity of 99.99% and a particle size of 400-600 mesh; Fe powder purity: 99.5%-99.9%, particle size 150-200 mesh; Ni powder purity: ≧99.9%, particle size 150-200 mesh; Al powder purity: ≧99.9%, particle size 150-200 mesh.
4. The process according to claim 1, wherein The assembly steps in step (2) are: a. Stack carbon source II, alloy catalyst, carbon source I, seed crystal, and thermal conductive sheet in order from top to bottom to form a block, which is a synthetic core column, and cover the synthetic core column with an insulating cup; b. Wrapping the heating carbon tubes around the structure obtained in step a, coating the top and bottom surfaces of the structure with dolomite insulation sheets, then coating the top and bottom surfaces of the dolomite insulation sheets with heating carbon sheets, and placing the wrapped structure into the insulation tubes to obtain a structural block; c. Place the structural block obtained in step b into the cavity of the pyrophyllite block, and set conductive plugs and insulation rings at the upper and lower ends of the structural block to obtain a synthetic block.
5. The process according to claim 1, wherein Step (3): The synthesis process is carried out using a six-sided top press. The pressure of the six-sided top press changes in the synthesis process in three stages, as follows: The first stage: the pressure is increased from 0 to P1 within 140-160 seconds. When the pressure reaches 30 MPa, heating begins; P1 is 100-120 MPa. The second stage: the pressure is maintained at P1, and the holding time is set to 10 to 20 days; The third stage: the pressure gradually decreases from P1 to P2 within 2000 seconds, and the P2 pressure is maintained for 1000~1100 seconds, and then reduced from P2 to 0 within 2000 seconds; P2 is 60~70MPa, and when the pressure is P2, the temperature in the synthesis chamber is 900-950℃; when the pressure is about to reach 0, the temperature in the synthesis chamber drops to 350-400℃.
6. The process according to claim 5, wherein In step (3), the power change and pressure change of the six-sided top press are carried out simultaneously, specifically in three stages, and the power change is as follows: Stage 1: When the pressure rises to 30 MPa, heating begins. At the same time, the power increases from 0 to W1 within 600 seconds. At this time, the temperature in the synthesis chamber reaches 1200-1350°C, and W1 is 7.8-8.0 kW. The second stage: when the pressure remains at P1, the power increases from W1 to W2 within 10 days, W2=W1+0.1KW; The third stage: As the pressure gradually decreases from P1 to 0, the power decreases from W2 to 0; at this time, the temperature in the synthesis chamber is between 330-400℃.
7. A large-sized cultivated diamond single crystal synthesized by the process according to any one of claims 1 to 6.
